Thermal computational model to predict thermal necrosis in bone sarcomas - Rua, Cláudia C. (2020)
Sarcomas are heterogeneous tumors that form frombonetissue, connective tissue, cartilaginous tissue,muscle tissue, adipose tissue, peripheral nerves, and blood vessels,usually atits extremities. These tumors occur at any age and in any region of the patient's body.